Digital Marketing and Handicraft Entrepreneurial Ventures in Tacna, Peru - Vilca Coaquera, Yaricsa Yuliana (2025)
The COVID-19 pandemic has accelerated the growth of e-commerce as a viable option for purchasing products and services online. This research study examines how the adoption of online technologies has impacted small craft producers in the cross-border region between Peru and Chile, particularly in the city of Tacna. We created web pages with online stores for 30 small craft producers and installed them on their smartphones. Additionally, they received training and were given autonomous management of the application. After two months, the web pages received 53,790 visits from the United States, Brazil, and Canada, highlighting the positive impact of technology adoption by small entrepreneurs. They were able to increase their sales and connect with customers worldwide, providing them with opportunities to enter export markets.